The Application of Islamic Business Ethics from the Perspective of Sheikh Yusuf al-Qaradawi (Case Study on Grocery and Vegetable Stores in Cimenyan, Bandung City) - Abdul Rofi Nursyamsi; Tarisa Dwi Putri Sujatna; Suhendi Suhendi (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This research aims to analyze the implementation of Islamic business ethics principles in business transactions at  Reni's store. Islamic business ethics emphasizes principles such as justice, the prohibition of usury and exploitation, honesty, and the ban of deceit in business activities, which are essential for creating fair and blessed transactions. Data were collected using a descriptive qualitative approach, observation, and direct interviews with the shop owner and several customers. The results show that  Reni's Store strives to apply the values of Islamic business ethics, such as transparency in pricing, honesty in transactions, and openness to customers. Although there are still challenges in daily practices, such as economic pressures and price competition, the implementation of these ethics has a positive impact on customer trust and business sustainability. This research is expected to provide valuable insights to small business owners in understanding the importance of Islamic business ethics in enhancing the blessings and sustainability of their businesses